Trauma emergency thoracotomy for resuscitation in shock—a multi-centre evaluation of current UK practice of pre-hospital and emergency department resuscitative thoracotomy in trauma. Issue 4 (13th October 2022) - Tucker, Harriet; Ramage, Lisa; Greenhalgh, Rob; Griggs, Jo; Lang, Nigel; Marsden, Max; Vulliamy, Paul; Wohlgemut, Jared M; Christian, Mike; Davenport, Ross
Abstract: Background: Resuscitative thoracotomy (RT) in traumatic cardiac arrest, in particular for penetrating trauma features within several national guidelines. However, evidence surrounding its practice is poor, consisting of predominantly small-scale observational studies. Survival is generally poor, estimated at 3–13%, with better outcomes in penetrating trauma. There is no national RT database and the Trauma Audit Research Network data misses those who have died pre-hospital. It is important that a more in-depth and accurate national picture of thoracotomy practice is developed nationally to guide future practice. Traumatic emergency thoracotomy for resuscitation in shock (TETRiS) is a multi-centre, prospective and observational evaluation of current RT practice in the UK. Aims and objectives: The aim of TETRiS is to evaluate the pathway of care for RT patients within the UK. This will be undertaken over a period of 12 months. This project will evaluate thoracotomies undertaken both pre-hospital and in emergency departments, examining various parameters including frequency, who performs the procedure, clinical indications, time from injury to initiation, mechanism of injury, injuries identified, interventions performed and patient outcomes. Methods: This project is being conducted as a collaboration between the National Trauma Research and Innovation Collaborative, the Pre-Hospital Trainee Operated Research Network, The Emergency Research Network and the National HEMS Research and Audit Forum (NHRAF). All UK HEMS, helicopter emergency medicine services and major trauma centre (MTCs) nationally have been recruited, with site investigators identified within each participating unit. Inclusion criteria: All patients undergoing RT, pre-hospital or in an MTC emergency department will be included.